Abdominal versus femoral subcutaneous fat gene expression in non-obese insulin resistant individuals - Badran, Saif; Almuraikhy, Shamma; Alser, Maha; Naja, Khaled; Anwardeen, Najeha; Abunada, Hanan H.; Ahmed, Mohamed Badie; Jarrar, Salma; Aljassem, Ghanem; Iskeirjeh, Sara; Hammouda, Atalla; Doi, Suhail A.; et al. (Frontiers in Endocrinology, 2026)
IntroductionAdipose tissue, once viewed primarily as an energy reservoir, is now recognized as an endocrine organ involved in various physiological functions, including energy balance and immune responses. Interestingly, recent insights suggest that not all overweight or obese individuals exhibit insulin resistance, guiding the focus towards depot-specific adipose gene expression and its metabolic implications. This pilot study investigates adipose depot-specific differences in gene expression in abdominal versus femoral subcutaneous adipose tissue (SAT) among non-obese, insulin-sensitive (IS) and insulin-resistant (IR) individuals, aiming to elucidate underlying mechanisms of metabolic dysfunction.MethodsSeventeen non-obese participants scheduled for body contouring surgery provided paired SAT biopsies from abdominal and femoral regions. Based on HOMA-IR scores, participants were categorized into IS and IR groups. Gene expression of key markers including GATA3, PPAR-γ, adiponectin, PGC-1α, TNF-α, and IL-6 were analyzed using real-time PCR and Western Blot. Vitamin D levels were also measured.ResultsOur analysis revealed a complex depot-specific regulation of GATA3 expression in human subcutaneous adipose tissue. While GATA3 protein showed a trend toward higher expression in abdominal SAT, its mRNA levels were significantly elevated in thigh SAT exclusively in insulin-resistant individuals. Furthermore, circulating vitamin D levels correlated significantly with GATA3 and PPARγ expression specifically in thigh adipose tissue.ConclusionThis pilot study reveals new evidence that the functional differences between abdominal and thigh subcutaneous adipose tissue also encompass transcriptional and post-transcriptional regulation of key adipogenic factors.